2010
DOI: 10.1152/ajpheart.00431.2009
|View full text |Cite
|
Sign up to set email alerts
|

Resistin decreases expression of endothelial nitric oxide synthase through oxidative stress in human coronary artery endothelial cells

Abstract: Resistin decreases expression of endothelial nitric oxide synthase through oxidative stress in human coronary artery endothelial cells. Am J Physiol Heart Circ Physiol 299: H193-H201, 2010. First published April 30, 2010 doi:10.1152/ajpheart.00431.2009.-Resistin is a newly discovered adipocyte-derived cytokine that may play an important role in insulin resistance, diabetes, adipogenesis, inflammation, and cardiovascular disease. However, it is largely unknown whether resistin impairs endothelial functions by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
124
2
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(139 citation statements)
references
References 55 publications
5
124
2
8
Order By: Relevance
“…This hormone has been shown to modulate phosphorylation of MAPK (ERK1/2, p38, and JNK; Di Simone et al 2009, Chen et al 2010, AKT (Palanivel et al 2006), and AMPK (Satoh et al 2004) in different cell types. These signaling pathways have been described to play a role in steroidogenesis and/or proliferation of GCs in response to various hormones such as FSH, IGF1, and insulin, as well as more recently to some adipokines including leptin and adiponectin (Moore et al 2001, Kayampilly & Menon 2004, Tosca et al 2005, Yu et al 2005, Ryan et al 2008, Kayampilly & Menon 2009).…”
Section: Role Of Resistin In Granulosa Cellsmentioning
confidence: 99%
“…This hormone has been shown to modulate phosphorylation of MAPK (ERK1/2, p38, and JNK; Di Simone et al 2009, Chen et al 2010, AKT (Palanivel et al 2006), and AMPK (Satoh et al 2004) in different cell types. These signaling pathways have been described to play a role in steroidogenesis and/or proliferation of GCs in response to various hormones such as FSH, IGF1, and insulin, as well as more recently to some adipokines including leptin and adiponectin (Moore et al 2001, Kayampilly & Menon 2004, Tosca et al 2005, Yu et al 2005, Ryan et al 2008, Kayampilly & Menon 2009).…”
Section: Role Of Resistin In Granulosa Cellsmentioning
confidence: 99%
“…This contrast could be caused by fact, that human and mouse RETN genes share only 53% homology, therefore their functions may differ between them [11] and other roles of RETN may exist in human. Although the exact function of resistin in human is still not known, increased resistin levels have been associated with coronary heart disease [12][13][14][15] and considered as a risk factor in gastric, colon and breast cancer [16][17][18][19], recently. The purpose of this case-control study was to determine the relationship between serum circulating resistin levels and resistin gene -420C>G (rs3219175) variant in endometrial cancer patients.…”
mentioning
confidence: 99%
“…Resistin impairs endothelial functions and causes the uptake of oxidized low density lipoprotein cholesterol and the formation of foam cells after being released by macrophages [39][40][41] . Resistin upregulates the release of adhesion molecules, increases the secretion of proinflammatory factors such as tumour necrosis factor-α, interleukin-6, interleukin-12, nitric oxide, endothelin-1 and matrix metalloproteinases and induces angiogenesis by increasing vascular epithelial growth factor (42)(43)(44)(45)(46)(47) . It has also been reported that resistin exerts a prothrombotic effect by inducing the secretion of tissue factor (48) .…”
Section: Discussionmentioning
confidence: 99%